European lampreys: new insights on postglacial colonization, gene flow and speciation - Mateus, Catarina Sofia (2016)
Ice ages are known to be the most dominant palaeoclimatic feature occurring on Earth, producing severe climatic oscillations and consequently shaping the distribution and the population structure of several species. Lampreys constitute excellent models to study the colonization of freshwater systems, as they commonly appear in pairs of closely related species of anadromous versus freshwater resident adults, thus having the ability to colonize new habitats, through the anadromous species, and establish freshwater resident derivates. We used 10 microsatellite loci to investigate the spatial structure, patterns of gene flow and migration routes of Lampetra populations in Europe. We sampled 11 populations including the migratory L. fluviatilis and four resident species, L. planeri, L. alavariensis, L. auremensis and L. lusitanica, the last three endemic to the Iberian Peninsula. In this southern glacial refugium almost all sampled populations represent a distinct genetic cluster, showing high levels of allopatric differentiation, reflecting long periods of isolation. As result of their more recent common ancestor, populations from northern Europe are less divergent among them, they are represented by fewer genetic clusters, and there is evidence of strong recent gene flow among populations. These previously glaciated areas from northern Europe may have been colonized from lampreys expanding out of the Iberian refugia. The pair L. fluviatilis/L. planeri is apparently at different stages of speciation in different locations, showing evidences of high reproductive isolation in the southern refugium, and low differentiation in the north.